Pengaruh Penyuluhan Kebencanaan Tanah Longsor terhadap Tingkat Pengetahuan dan Sikap Siswa di SMPN 3 Pancur Batu - Nanda, Meutia; Lubis, Siti Hajar; Redha, Satia; Ginting, Dafina Hilya Fatiha; Indriawati, Astrid Fhira; Ginting, Muhammad Ramadhan (Yayasan Jompa Research and Development, 2026)
Landslides are geological phenomena that occur when unstable soil, rocks, or other materials fall to the bottom of the impact site. The purpose of this study was to determine the effect of landslide disaster education on the level of knowledge and attitude change of students at SMPN 3 Pancur Batu. Landslide disaster education is the implementation of a problem-solving plan used to address low levels of knowledge and preparedness. The research method used was quantitative with a quasi-experimental design using a one-group pre-test post-test design. The population for this study was all ninth-grade students, with a sample size of 64 students selected using purposive sampling. The instrument for this research was a closed questionnaire consisting of 10 knowledge questions and 10 attitude questions using a Likert scale. Data analysis was performed using univariate and bivariate analysis with a paired sample t-test. The results showed an increase in the average knowledge score of students from 31.72 to 34.22 with a p-value of 0.0001, indicating a significant effect of counseling on student knowledge. In addition, the average attitude score also increased from 33.38 to 34.33 with a p-value of 0.006, indicating a significant effect of the counseling on changes in student attitudes. The conclusion of this study is that landslide disaster counseling is effective in increasing knowledge and shaping students' attitudes of preparedness towards the risk of landslide disasters.